2021
DOI: 10.3233/jad-200821
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prediction of Imminent Progression to Clinically Significant Memory Decline Using Surface Multivariate Morphometry Statistics and Sparse Coding

Abstract: Background: Besides their other roles, brain imaging and other biomarkers of Alzheimer’s disease (AD) have the potential to inform a cognitively unimpaired (CU) person’s likelihood of progression to mild cognitive impairment (MCI) and benefit subject selection when evaluating promising prevention therapies. We previously described that among baseline FDG-PET and MRI measures known to be preferentially affected in the preclinical and clinical stages of AD, hippocampal volume was the best predictor of incident M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The second contribution is that the FMFS is an effective tool to select and visualize the brain imaging feature data. In our previous studies (Stonnington et al, 2021;Zhang et al, 2021a,b), the morphometry features always showed excellent performance in predicting AD progression. However, the major limitation of these works was that they failed to visualize the disease-related regions on the surfaces.…”
Section: Discussionmentioning
confidence: 74%
“…The second contribution is that the FMFS is an effective tool to select and visualize the brain imaging feature data. In our previous studies (Stonnington et al, 2021;Zhang et al, 2021a,b), the morphometry features always showed excellent performance in predicting AD progression. However, the major limitation of these works was that they failed to visualize the disease-related regions on the surfaces.…”
Section: Discussionmentioning
confidence: 74%
“…The second contribution is that the FMFS is an effective tool to select and visualize the brain imaging feature data. In our previous studies (Stonnington et al, 2021;Zhang et al, 2021aZhang et al, , 2021b, the morphometry features always showed excellent performance in predicting AD progression. However, the major limitation of these works was that they failed to visualize the disease-related regions on the surfaces.…”
Section: Discussionmentioning
confidence: 74%
“…[30][31][32]We also performed surface smoothing to reduce the noise, followed by mesh simplification and refinement using the same method as our previous work [40–42]. A conformal grid of size 150*100 was computed on each surface using a holomorphic 1-form basis [43,44], followed by the computation of conformal factor and mean curvature on each point and a surface fluid registration method to register the hippocampal surfaces to a template surface [45–47][40] For more details, refer to [45].…”
Section: Methodsmentioning
confidence: 99%
“…We took advantage of our previously established pipeline protocol for hippocampus segmentation and image registration [14,28,29], which employs FMRIB's Integrated Registration and Segmentation Tool (FIRST) for automatic segmentation, a topology-preserving level set method combined with marching cubes algorithm for hippocampal surface reconstruction [37][38][39]. [30][31] [32]We also performed surface smoothing to reduce the noise, followed by mesh simplification and refinement using the same method as our previous work [40][41][42]. A conformal grid of size 150*100 was computed on each surface using a holomorphic 1-form basis [43,44], followed by the computation of conformal factor and mean curvature on each point and a surface fluid registration method to register the hippocampal surfaces to a template surface [45][46][47][40] For more details, refer to [45].…”
Section: Hippocampus Segmentation and Surface Registrationmentioning
confidence: 99%